Is Europe strategically autonomous in defense? - Martí, Carlos (Papeles de Europa, 2017)
This article analyses if Europe owns the institutions, resources, means and industrial infrastructure to be autonomous in the execution of military missions aimed at providing security and defence. In particular, the key aspects related to the acquisition of military capabilities and the generation of forces to perform such missions, as well as the technological and industrial capabilities that assure the supply of the means associated to these capabilities without depending on other countries, in particular the United States. The analysis suggests that Europe has a long and winding road to achieve such strategic autonomy.
Keywords: Strategic autonomy; Common Defence and Security Policy